PERPUSTAKAAN OTOMATIS JURUSAN FISIKA FMIPA UNIVERSITAS CENDERAWASIH BERBASIS SLIMS-7 CENDANA - Endang Haryati; Steven Y.Y. Mantiri (LPPM Uncen, 2018)
The automated library system has been applied to the library of Department of Physics FMIPA Cendrawasih University. An automated library system is a library system by combining software and hardware to generate digital libraries that can be accessed digitally. The purpose of this community service is to apply the SLIMS-7 (Senayan Library Management System-7) Cendana software at the library of Department of Physics FMIPA Cendrawasih University. The target community of this activity are students and lecturers of Departement of Physics FMIPA Cenderawasih University. The results show that the library management system is getting better and controllable. Futhermore, the activity of library users has been increased.Keywords: Automatic library, Department of Physics FMIPA Cenderawasih University, SLIMS-7 Cendana